Enhance Work Performance Through Employee Involvement Strategy - V., Vijayakumar (2000)

(untitled)
Electricity power industry in Malaysia has been operating in environments of intense and rapid change. Technology advancement has forced customers to demand for services from the utilities. Customers demand for quality product and services had launched the search by the utility companies for best strategy to satisfy their needs. At TNB Bagan Serai, the high rate of low voltage power failures during the middle of nineties has caused the organization faced with pressure from both customers as well as top management. The earlier application of the Conventional Method through tall hierarchy did not help to solve the problem. Many strategies were outlined but it failed to produce promising results. During the month of July 1996, a new strategy as known as Employee Involvement Participation Method was introduced in order to overcome power outages issue. Since the causes of the outages were identified due to human factor and method factor, a severe focus on technical and non-technical issues were enhanced. Emphasis getting job done through employee involvement was enhanced. As a result, the power outages rate of 306 in September 1995 was reduced to 43 by end of April 1997 and settled below 15 a month by end of December 1999. This paper explains the experiences encountered by TNB Bagan Serai to achieve an excellent result and how they manage to transform the employees from various ethic background with different level of age to unite in a team with one vision: reduce power outages. An interview survey regarding the effectiveness of two different management methods was conducted between 24th Jan 2000 to 30th Jan 2000. The result of this survey is discussed in this paper.